Unveiling the unknown phylogenetic position of the scallop Austrochlamys natans and its implications for marine stewardship in the Magallanes Province - Rosenfeld, Sebastian; Aldea Venegas, Cristian Leonardo; Lopez, Zambra; Maturana, Claudia S.; Ojeda Villarroel, Jaime Andrés; Bahamonde, Francisco; Detree, Camille; Mansilla Muñoz, Andres Omar; Poulin, Elie; Gerard, Karin Francoise (My University, 2021)
Two species of scallop, Austrochlamys natans ("Ostion del Sur") and Zygochlamys patagonica ("Ostion patagonico") are presently exploited in the southern part of the Magallanes Province (MP). The lack of clarity in taxonomic identification and ecological aspects is generating both erroneous extraction statistics and an unperceived harvesting pressure on A. natans and Z. patagonica. We aim to discriminate these Magallanes scallops accurately, improve our understanding of their complex natural history and discuss possible implications for their management and conservation status, given the current fisheries statistics. To achieve these goals, we present a complete review of the historical identification of the Magallanes scallop and a multi-locus molecular phylogeny which allowed us to recover the phylogenetic position of A. natans. We sampled 54 individuals from five localities across the southern Pacific coast of the MP. We calculated the depth of the byssal notch (BND) and shell height (VH) ratio from morphological characters and conducted phylogenetic reconstructions with mitochondrial (12S and 16S) and nuclear markers (28S) using Bayesian and maximum likelihood analyses. Both morphology and molecular phylogeny identified two distinct entities, Z. patagonica and a distinct, highly divergent lineage that corresponds to A. natans. Our study provides integrative evidence to alert the current fishery management and the need for further conservation studies.
Keywords: Lineage (genetic)